Math, asked by Anonymous, 1 year ago

Factorise x^2-5x+6
Give step by step solution

Answers

Answered by Anonymous
7
Hey!!!...Here is ur answer

x^2-5x+6

x^2-3x-2x+6

x (x-3)-2 (x-3)

(x-3)(x-2)

Hope it will help you
Answered by MarkAsBrainliest
12
\textbf{- Answer -}

Now, \: \: {x}^{2} - 5x + 6 \\ \\ = {x}^{2} - (3 + 2)x + 6 \\ \\ = {x}^{2} - 3x - 2x + 6 \\ \\ = x(x - 3) - 2(x - 3) \\ \\ = (x -3 )(x - 2), \\ \\ which \: \: is \: \: the \: \: required \: \: \\ factorization.

#\textbf{MarkAsBrainliest}
Similar questions